Air pollution and outpatient visits for conjunctivitis: A case-crossover study in Hangzhou, China. (December 2017) - Fu, Qiuli; Mo, Zhe; Lyu, Danni; Zhang, Lifang; Qin, Zhenwei; Tang, Qiaomei; Yin, Houfa; Xu, Peiwei; Wu, Lizhi; Lou, Xiaoming; Chen, Zhijian; Yao, Ke
Abstract: BACKGROUND: Conjunctivitis, one of the most common ocular surface diseases, can be caused by many factors. OBJECTIVES: The objective of this study was to investigate the potential association between conjunctivitis and air pollutants. MATERIALS AND METHODS: Data of 9737 outpatient visits for conjunctivitis from July 1, 2014 to June 30, 2016 were obtained from the Eye Center of the Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, China. The data were linked to data on the concentrations of carbon monoxide (CO), nitrogen dioxide (NO2 ), ozone (O3 ), sulfur dioxide (SO2 ), and fine particulate matter with a median aerometric diameter of less than 10 and 2.5 μm (PM10 and PM2.5, respectively), which were obtained from the Environmental Protection Department of Zhejiang Province. A time-stratified case-crossover study design and conditional logistic regression were applied to analyze the association between air pollutants and outpatient visits for conjunctivitis. RESULTS: A 10 μg/m 3 increase in PM10, PM2.5, SO2, NO2, and CO concentrations on the same day as the hospital visit or on lag days before the hospital visit date was associated with outpatient visits for conjunctivitis. The strongest association was observed between SO2 and conjunctivitis patients aged 2–5 years. Variation occurs between warm and cold seasons, between genders, and among different age groups. CONCLUSIONS: Our study provided evidence that outpatient visits for conjunctivitis were significantly associated with air pollution in Hangzhou, China. Graphical abstract: Highlights: A time-stratified case-crossover design was applied in the present study. Conjunctivitis outpatient visits were related to air pollutants in Hangzhou, China. Sulfur dioxide (SO2 ) showed the strongest association with patients aged 2–5 years. Variations were revealed between seasons, genders, and among different age groups.